(untitled) (Praxis Educativa, 2025)
This essay explores the complex situation of the colonized in relation to others and to their own projection of guilt and inferiority due to the racism and unparalleled violence of the colonial system. The intersection of objective and historical conditions is central, but not sufficient. Self-evaluation in psychological terms is not enough, especially because recognition, in Frantz Fanon’s view, has a social function. This proposed theory of recognition is considered emancipatory when there is a history and epistemology that make being and decolonization plausible from the perspective of the subject himself, leaving behind the zone of non-being to open up decolonizing possibilities.